E-REGISTRATION AND HEALTH SERVICE CONSULTATION USING AGILE METHODS - Pascal Sjach Fahlevi; Agus Iskandar (Adisam Publisher, 2024)
This research focuses on developing an E-Registration and Health Services Consultation system using the Agile method, which aims to increase the efficiency and effectiveness of health services. The main objective of this research is to design and implement a system that can make it easier for patients to register and consult online, reduce waiting time, and improve the quality of interactions between patients and health service providers. This research is motivated by the need to overcome the problem of limited access and inconvenience in conventional health services, which often require long waiting times and complicated administrative processes. Agile methods were chosen for their flexibility and adaptivity in software development, allowing development teams to respond quickly to changing user needs and preferences. This research uses an iterative approach, where development is carried out in cycles consisting of planning, design, implementation, testing and evaluation. Data was collected through user satisfaction surveys, interviews with stakeholders, and system performance analysis. The findings of this research indicate that the implementation of the E-Registration and Health Services Consultation system can significantly increase patient satisfaction, with a decrease in average waiting time and an increase in service accessibility. Apart from that, this system also supports better decision making by health service providers through integrated and real-time patient data management. This research makes an important contribution to the development of health information systems, offering valuable insights into the application of Agile methods in the development of responsive and user-centered health care systems.